1996
DOI: 10.1074/jbc.271.3.1301
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Contact Sites in the Actin-Thymosin β4 Complex by Distance-dependent Thiol Cross-linking

Abstract: Binding sites of actin and thymosin ␤4 were investigated using a set of bifunctional thiol-specific reagents, which allowed the insertion of cross-linkers of defined lengths between cysteine residues of the complexed proteins. After the cross-linkers were attached to actin specifically at either Cys 10 , Cys 374 , or to the sulfur atom of the ATP analog adenosine 5-O-(thiotriphosphate) (ATP␥S), the actin derivatives were reacted with synthetic thymosin ␤4 analogs containing a cysteine at one of the positions 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…This was confirmed by the observation that the increase in absorbance was paralleled by a corresponding increase of a 47 kDa band in SDS-PAGE, representing the conjugate of the actin derivative (42 kDa) and the TIM analog (5 kDa) [12]. In the present study a similar 47 kDa band was found (see below), indicating that even in the presence of DNase I the crosslinking reaction had proceeded specifically.…”
Section: Resultssupporting
confidence: 74%
See 4 more Smart Citations
“…This was confirmed by the observation that the increase in absorbance was paralleled by a corresponding increase of a 47 kDa band in SDS-PAGE, representing the conjugate of the actin derivative (42 kDa) and the TIM analog (5 kDa) [12]. In the present study a similar 47 kDa band was found (see below), indicating that even in the presence of DNase I the crosslinking reaction had proceeded specifically.…”
Section: Resultssupporting
confidence: 74%
“…The sole exposed thiol group of actin (cysteine 374) was selectively modified, via a disulfide bridge, with a 9.2 ,A linker bearing a thiol-capturing moiety (reaction 1). In a previous study [12] we demonstrated that the resulting actin derivative binds TIM, as well as the analog Cys6TIM, with an affinity comparable to that shown by actin itself [12]. On the addition of Cys6TIM, complex formation leads to a high-yield crosslinking reaction, which can be followed spectrophotometrically from the release of a stoichiometric amount of 2-nitro-5-thiobenzoate (reaction 2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations